The elusiveness of tolerance : the "Jewish question" from Lessing to the Napoleonic Wars - Erspamer, Peter R. (University of North Carolina studies in the Germanic languages and literatures, 2020)
Analyzing literary works - from Lessing's "Nathan der Weise" (1779) to Sessa's "Unser Verkehr" (1812/15) - and political and philosophical tracts, shows the transition from an enlightened, emancipatory literature to an antisemitic literature in the early 19th century. The ideology of tolerance failed because of its internal contradictions.